Millennial scale impact on the marine biogeochemical cycle of mercury from early mining on the Iberian Peninsula. Issue 1 (24th January 2013) - Serrano, O.; Martínez‐Cortizas, A.; Mateo, M.A.; Biester, H.; Bindler, R.
<x xml:space="preserve">Abstract</x> [1] The high‐resolution mercury record of a Posidonia oceanica mat in the northwest Mediterranean provides an unprecedented testimony of changes in environmental mercury (Hg) loading to the coastal marine environment over the past 4315 yr BP. The period reconstructed made it possible to establish tentative preanthropogenic background Hg levels for the area (6.8 ± 1.5 ng g–1 in bulk sediments). A small, but significant, anthropogenic Hg increase was identifiable by ~2500 yr BP, in agreement with the beginning of intense mining in Spain. Changes in the record suggest four major periods of anthropogenic Hg pollution inputs to the Mediterranean: first, during the Roman Empire (2100–1800 yr BP); second, in the Late Middle Ages (970–650 yr BP); third, in the modern historical era (530–380 yr BP); and fourth, in the industrial period (last 250 years), with Hg concentrations two‐, four‐, five‐, and tenfold higher than background concentrations, respectively. Hg from anthropogenic sources has dominated during the last millennium (increase from ~12 to ~100 ng g–1), which can be related to the widespread historical exploitation of ore resources on the Iberian Peninsula. The chronology of Hg concentrations in the mat archive, together with other Hg pollution records from the Iberian Peninsula, suggests regional‐scale Hg transport and deposition and shows earlier marine Hg pollution than elsewhere in Europe. Moreover, the mat also records a higher number of historic contamination phases, in comparison with other natural archives, probably due to the fact that the bioaccumulating capacity of P. oceanica magnify environmental changes in Hg concentrations. In this study, we demonstrate the uniqueness of P. oceanica meadows as a long‐term archive recording trends in Hg abundance in the marine coastal environment, as well as its potential role in the Mediterranean as a long‐term Hg sink.